2019
DOI: 10.3390/cryst9050259
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Effect on the Crystallization of Mineral Phases in a Solution Simulating Human Urine

Abstract: The effect of bacteria that present in the human urine (Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Staphylococcus aureus) was studied under the conditions of biomimetic synthesis. It was shown that the addition of bacteria significantly affects both the phase composition of the synthesized material and the position of crystallization boundaries of the resulting phosphate phases, which can shift toward more acidic (struvite, apatite) or toward more alkaline (brushite) conditions. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Similar results were observed in the synthetic urine supplemented with peptone. Previous studies have also provided evidence from in vitro studies that peptone influences the growth and pH of the synthetic urine and modulates the lithogenesis in a lower pH than needed under normal conditions [ 27 ]. The bacterium was tolerant to wide range of pH (5–10) giving advantages for its survival in the fluctuating urine ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were observed in the synthetic urine supplemented with peptone. Previous studies have also provided evidence from in vitro studies that peptone influences the growth and pH of the synthetic urine and modulates the lithogenesis in a lower pH than needed under normal conditions [ 27 ]. The bacterium was tolerant to wide range of pH (5–10) giving advantages for its survival in the fluctuating urine ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have proposed that struvite formation by microorganisms results from the release of ammonium either by decomposition of organic material or by hydrolysis of urea by urease by the microorganism resulting in the accumulation of ammonium ions in urine [ 32 , 36 ]. However, there is limited evidence of this [ 27 ]. Our experimental results provide further evidence of the production of ammonia and media alkalization by YU22 by breaking down amino acids and peptides.…”
Section: Discussionmentioning
confidence: 99%
“…The use of balanced filtering in dual energy technique was applied by Saito [29] in order to achieve a signal-to-noise ratio of 5 in the final dual energy subtracted iodine image. Although the appearance of calcifications may indicate breast cancer, the consistency of calcifications will indicate whether they are associated with malignancy or benignancy [69][70][71][72][73][74][75][76][77][78][79][80][81]87]. Martini et al [28] worked on the differentiation of calcifications consisting of minerals found to indicate malignancy and benignancy according to literature [103][104][105].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, calcifications are divided into Type I and Type II [69][70][71][72][73][74][75]. The calcifications of Type I are composed calcium oxalate (CaC2O4) crystals [76] and are found to be associated with benign lesions or mostly non-invasive lobular carcinoma in situ [77,78]. The calcifications of Type II are composed of calcium phosphate, mainly hydroxyapatite (Hap) crystals [76,[79][80][81] and in some cases of calcium carbonate (CaCO 3 ).…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation